2017
DOI: 10.1039/c7ta07999k
|View full text |Cite
|
Sign up to set email alerts
|

MXene/graphene hybrid fibers for high performance flexible supercapacitors

Abstract: Continuous MXene/graphene fibers are fabricatedviawet-spinning assembly strategy, from which fiber-constructed supercapacitors are obtained that exhibit both high capacitance and flexibility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
265
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 398 publications
(285 citation statements)
references
References 41 publications
7
265
1
Order By: Relevance
“…Comparably, the MXene/CNT fiber‐based device also exhibits a rectangular‐shaped CV behavior with a significantly enhanced current density (Figure b), which is attributed to the pseudocapacitive contribution from MXene nanosheets. The rate capability of the MXene/CNT fiber‐based device is remarkable with capacitance retention of 72% at 100 mV s −1 (Figure S10, Supporting Information), which is superior to that of MXene/rGO fiber‐, MXene/Ag/nylon fiber‐, MXene/stainless steel wire‐based devices, the capacitance retention of which is normally less than 50% within scan rate range from 5 to 100 mV s −1 . This performance is also comparable to that of MXene/graphene hybrid film measured in aqueous electrolyte .…”
mentioning
confidence: 81%
“…Comparably, the MXene/CNT fiber‐based device also exhibits a rectangular‐shaped CV behavior with a significantly enhanced current density (Figure b), which is attributed to the pseudocapacitive contribution from MXene nanosheets. The rate capability of the MXene/CNT fiber‐based device is remarkable with capacitance retention of 72% at 100 mV s −1 (Figure S10, Supporting Information), which is superior to that of MXene/rGO fiber‐, MXene/Ag/nylon fiber‐, MXene/stainless steel wire‐based devices, the capacitance retention of which is normally less than 50% within scan rate range from 5 to 100 mV s −1 . This performance is also comparable to that of MXene/graphene hybrid film measured in aqueous electrolyte .…”
mentioning
confidence: 81%
“…PPy, with its intrinsic highly redox active behavior and good conductivity, has been employed in composites with MXene to enhance the performance of supercapacitors . Nevertheless, the performance is far from optimal owing to lack of good synthesis methods.…”
Section: Introductionmentioning
confidence: 99%
“…[69] Besides, Fan et al also reported a method of growing 2D layer Mo 2 C on vertically distributed graphene, which was obtained from vertically distributed CNTs. [131,[140][141][142] Our group directly synthesizes TI 3 C 2 T x / rGO composite by solution mixing and has successfully infiltrated sulfur into the resulting composite. In order to deposit MoC 2 on the surface of graphene uniformly, molybdenum metal must be first sprayed on the surface of graphene, and then the Mo-based precursor is carbonized with a gaseous carbon source to form 2D layer Mo 2 C. [130] Figure 3b shows the schematic preparation process of the Mo 2 C/N-doped graphene (N-G) composite.…”
Section: Mxene-graphene Compositesmentioning
confidence: 99%
“…Furthermore, rGO films and Ti 3 C 2 T x films are flexible, so the Ti 3 C 2 T x /rGO flake can be even more flexible. [142] In MXene/CNT composites, not only do the CNTs have similar performance with the rGO, but also the CNTs can form a 3D electric network to link near and far MXene layers. [141,142] MXene/rGO composites have had their structure optimized by specific technologies to exhibit better performance.…”
Section: Wwwadvmatinterfacesdementioning
confidence: 99%